The application of STAD-Cooperative Learning Model: Efforts to increase motivation and Learning Outcomes of students in Class 5 SD N 07 Ledok Salatiga in Mathematics subjecth in Folding Symmetry and Rotating Symmetry topics - HM Munawar (Prodi PGMI IAIN Salatiga, 2019)
This study aims to improve the motivation and mathematical achievement of a two-dimensional figure about folding symmetry and rotary symmetry for fifth-grade students of SD Negeri Ledok 07 Salatiga in the even semester of 2018/2019. This research was conducted in the fifth grade of SD Negeri Ledok 07 Salatiga for one semester. Subjects in the study were all fifth-grade students as many as 23 students, consisting of 12 women and 11 men. This study used two cycles of action. In each cycle, it was carried out in 4 stages, namely planning, acting, observing, and reflecting. The data collection was through documentation, observation, and test results. Whereas, the research instruments were in the form of a list of values, observation sheets, and written questions. Data were obtained from observers, consisting of teachers as collaborators and the lesson grid. Data analysis used comparative descriptive followed by reflection. In the initial conditions, it turned out that learning outcomes were still low, as evidenced by students who scored 70 or more were still seven students (34.8%). In the first cycle, students who scored 70 or more were 15 students (65.2%). In cycle II, students who scored 70 or more increased to 21 students (91.3). Then, it can be concluded that the Student Team Achievement Division model can improve motivation and learning outcomes for mathematics in the fifth grade at SD Negeri Ledok 07 Salatiga in the second semester of 2018/2019.